Desmoid-type fibromatosis. Issue 9 (September 2015) - Otero, S.; Moskovic, E.C.; Strauss, D.C.; Benson, C.; Miah, A.B.; Thway, K.; Messiou, C.
<x xml:space="preserve">Abstract</x> Desmoid-type fibromatosis is a rare, locally infiltrative, mesenchymal neoplasm that is associated with high rates of local recurrence but lacks the potential to metastasise. The disease affects younger individuals, with a peak age of 30 years, and is the most common cause of an anterior abdominal wall mass in young women of childbearing age. It may, however, involve nearly every body part, including the extremities, head and neck, trunk, and abdominal cavity; as such, desmoid-type fibromatosis may present to a range of general and subspecialty radiologists. These rare tumours have a widely variable clinical presentation and unpredictable natural history, hence input from a soft-tissue tumour centre is recommended, although much of the imaging may be performed at the patient's local hospital. The consensus for treatment has changed over the past decade, with most centres moving away from primary radical surgery towards a front-line 'watch-and-wait' policy. Therefore, imaging has an increasingly important role to play in both the diagnosis and follow-up of these patients. This review will discuss the typical imaging characteristics of these lesions and suggest diagnostic and follow-up magnetic resonance imaging protocols, with details of suitable sequences and scanning intervals.